1993
DOI: 10.2307/3350399
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Studies of State Drug Reimbursement Policies: Research in Need of Discipline

Abstract: Concerns over pharmaceutical costs and appropriateness of medication use have led state Medicaid programs to restrict drug reimbursement. This article critically reviews 20 years of research on cost sharing, drug reimbursement limits, and administrative limitations on access to particular drugs via formularies, category exclusions, or prior authorization requirements; evaluates their methodological rigor; summarizes the state of current knowledge; and proposes future research directions. Drug reimbursement cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 31 publications
1
85
1
1
Order By: Relevance
“…Increases in out-of-pocket treatment expenses will invariably result in more patients choosing not to treat, consequentially increasing the prevalence of undertreated chronic diseases (e.g., hypertension). [10][11][12] Furthermore, increasing the patient's responsibility in deciding whether to initiate or continue treatment will make patients' nonmedical characteristics (e.g., expected quality of life and health expectations, level of education, and health insurance coverage) much more salient in the decision-making process. 13 Because these factors correlate with socioeconomic class, a shift in responsibility for personal health (financial and otherwise) could result in further social inequities in health outcomes.…”
mentioning
confidence: 99%
“…Increases in out-of-pocket treatment expenses will invariably result in more patients choosing not to treat, consequentially increasing the prevalence of undertreated chronic diseases (e.g., hypertension). [10][11][12] Furthermore, increasing the patient's responsibility in deciding whether to initiate or continue treatment will make patients' nonmedical characteristics (e.g., expected quality of life and health expectations, level of education, and health insurance coverage) much more salient in the decision-making process. 13 Because these factors correlate with socioeconomic class, a shift in responsibility for personal health (financial and otherwise) could result in further social inequities in health outcomes.…”
mentioning
confidence: 99%
“…As mentioned above, the benefits structure of Fair PharmaCare was designed so that approximately 60% of seniors would experience no significant changes in cost sharing. This makes the current Fair PharmaCare Program for seniors quite different from other cost-sharing policies that have been investigated by others (Soumerai et al 1987(Soumerai et al , 1993Tamblyn et al 2001). However, Fair PharmaCare for future seniors -those born after 1939, including the sizable cohort of baby boomers -will be the same as Fair PharmaCare for non-seniors (Morgan and Coombes, page 92).…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has found adverse health outcomes in jurisdictions that reduced drug plan spending through the implementation of co-payments or prescription limits (Soumerai et al 1987(Soumerai et al , 1993Tamblyn et al 2001). BC policy makers hoped to minimize the potential for such reductions in access to medicines among seniors (Morgan and Coombes, page 92).…”
Section: Impact On Accessmentioning
confidence: 99%
“…In particolare, l'impatto avuto sulla spesa farmaceutica totale, sui costi totali del sistema sanitario e sugli esiti sanitari non è noto. Il lavoro di Soumerai ed altri lavori mostrano come le politiche che limitano l'accesso del pubblico alle corrette terapie farmacologiche spesso portino involontariamente ad un aumento delle visite dal medico, dei ricoveri ospedalieri e dell'utilizzo di case di cura (12)(13)(14)(15)(16). Questi servizi sono più costosi, oltre a riflettere un peggioramento dello stato di salute dei pazienti.…”
Section: Discussioneunclassified